STRATEGI MANAJEMEN KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDIT IMAM SYAFII CENDIKIA PEKANBARU - Asy Syifa Fitrah Syahidah; Ruri Liana Anugrah (STKIP Pesisir Selatan, 2026)
This study aims to describe classroom management strategies in improving students' learning motivation at SD IT Imam Syafii Cendikia Pekanbaru and to identify the supporting and inhibiting factors in their implementation. This research employed a descriptive qualitative approach through field research. Data were collected through observations, semi-structured interviews, and documentation involving teachers and students. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that classroom management strategies were implemented through diagnostic assessments, the establishment of classroom rules and routines, student grouping based on learning styles, active and enjoyable learning activities, teachers’ personal approaches to students, and the integration of Islamic values into the learning process. These strategies positively influenced students’ learning motivation, as reflected in increased participation, enthusiasm, self-confidence, responsibility, and engagement in classroom activities. Supporting factors included teacher competence, parental support, adequate facilities, and a conducive school environment, while inhibiting factors consisted of diverse student characteristics, inconsistent discipline, and limited instructional time. This study highlights the integration of classroom management practices with Islamic values as a distinctive strategy that simultaneously strengthens students’ academic motivation, character development, and spiritual growth in an Integrated Islamic Elementary School context.